TRANSGENDERS’ PERCEPTION TOWARDS THEIR LIFESTYLE: A SPECIAL REFERENCE TO KALABURAGI DISTRICT (International Journal of Food and Nutritional Sciences, 2023)
This study is related to the lifestyle of TGs, data were collected after getting the informed consent from each subject. A total of 50 transgenders were enrolled in this study, primary data collected from transgender people through field survey by seeking information from the TG associations in Kalaburagi district. The majority 49 (98%) respondents were considered as a TG from male to female gender, 41 (82%) respondents in Kalaburagi district Transgender are Hindus, a maximum of 18 (36%) respondents are sex workers, 23 (46%) respondents faces discriminations from all of these means by Police, Health care people, Public, Public transportation and Employer, 16 (32%) respondents don’t have any kind of habits like alcohol consuming, Smoking, Chewing etc. and 40 (80%) transgender people told agreed with the guru - chela structure of this community. They should be educated and motivated to overcome the barriers and seek professional work in society. This necessitates a tailored intervention to satisfy the needs of this population in future.